Transposon-Derived Non-coding RNAs and Their Function in Plants - Cho, Jungnam (Frontiers in Plant Science, 2018)
Transposable elements (TEs) are often regarded as harmful genomic factors and indeed they are strongly suppressed by the epigenetic silencing mechanisms. On the other hand, the mobilization of TEs brings about variability of genome and transcriptome which are essential in the survival and evolution of the host species. The vast majority of such controlling TEs influence the neighboring genes in cis by either promoting or repressing the transcriptional activities. Although TEs are highly repetitive in the genomes and transcribed in specific stress conditions or developmental stages, the trans-acting regulatory roles of TE-derived RNAs have been rarely studied. It was only recently that TEs were investigated for their regulatory roles as a form of RNA. Particularly in plants, TEs are ample source of small RNAs such as small interfering (si) RNAs and micro (mi) RNAs. Those TE-derived small RNAs have potentials to affect non-TE transcripts by sequence complementarity, thereby generating novel gene regulatory networks including stress resistance and hybridization barrier. Apart from the small RNAs, a number of long non-coding RNAs (lncRNAs) are originated from TEs in plants. For example, a retrotransposon-derived lncRNA expressed in rice root acts as a decoy RNA or miRNA target mimic which negatively controls miRNA171. The post-transcriptional suppression of miRNA171 in roots ensures the stabilization of the target transcripts encoding SCARECROW-LIKE transcription factors, the key regulators of root development. In this review article, the recent discoveries of the regulatory roles of TE-derived RNAs in plants will be highlighted.